Multiple positive solutions of a singular fractional differential equation with negatively perturbed term - Zhang, X.; Liu, L.; Wu, Yong Hong (Pergamon, 2012)
Let View the MathML sourceD0+α be the standard Riemann–Liouville derivative. We discuss the existence of multiple positive solutions for the following fractional differential equation with a negatively perturbed termView the MathML source{−D0+αu(t)=p(t)f(t,u(t))−q(t),0<t<1,u(0)=u′(0)=u(1)=0,[Turn MathJax on]where 2<α≤32<α≤3 is a real number, the perturbed term q:(0,1)→[0,+∞)q:(0,1)→[0,+∞) is Lebesgue integrable and may be singular at some zero measures set of [0,1], which implies the nonlinear term may change sign.